Variance in the valenced response during moderate-to-vigorous physical activity: a review of cognitive and contextual mechanisms. Issue 1 (1st January 2021) - Bourke, Matthew; Hilland, Toni A.; Craike, Melinda
ABSTRACT: It is hypothesised that various factors may explain variation in the valenced (pleasure-displeasure) response to moderate-to-vigorous physical activity (MVPA), however the empirical evidence for these factors has not been reviewed. This narrative review summarises empirical evidence relating to cognitive and contextual mechanisms that may explain inter- and intra-individual variation in the valenced response to MVPA. The mechanisms included in this review include (i) cognitive factors: motivation, autonomy, competence, task self-efficacy, attentional focus and relatedness, (ii) the social context, and (iii) the physical environment. The electronic databases Medline, PsychINFO and SPORTDiscus were searched to identify relevant articles. Different factors may explain inter- and intra-individual variations in the valenced response to MVPA. Factors that consistently explain inter-individual variations in the valenced response to MVPA include self-determined motivation, physical activity competence and task self-efficacy. Considering intra-individual variations, people may have a more pleasurable experience during MVPA when they have more dissociative thoughts, and when they participate in the MVPA outdoors. Implications of these findings are discussed and future research directions are suggested.